Massive pulmonary thromboembolism in a pediatric patient with eosinophilic granulomatosis with polyangiitis: a case-based review emphasizing management - Batuhan Küçükali; Merve Yazol; Çisem Yıldız; Büşra Acun; Nuran Belder; Nihal Karaçayır; Merve Kutlar; Pelin Esmeray Şenol; Zühre Kaya; Deniz Gezgin Yıldırım; Sevcan A. Bakkaloğlu (Pediatric Rheumatology Online Journal)
Abstract Background Pediatric patients with Eosinophilic Granulomatosis with Polyangiitis (EGPA) are at an increased risk of arterial and venous thromboembolism (AVTE). Although the exact mechanisms underlying AVTE remain unclear, eosinophils play a pivotal role in AVTE. Main body Current guidelines lack evidence-based recommendations, particularly concerning anticoagulant and antiplatelet treatments for this condition. Herein, we document a pediatric EGPA patient with deep venous thrombosis presenting with massive pulmonary thromboembolism during a relapse, treated with immunosuppressive and anticoagulant therapy to raise awareness among clinicians. Additionally, we performed a literature review to highlight various aspects of pediatric AVTE. Moreover, we evaluated the management strategies employed for the patients identified in the literature review and summarized the current practice guidelines regarding pediatric EGPA patients with AVTE to provide recommendations to clinicians on the management of this challenging complication. Conclusions Most AVTE events occur during periods of high disease activity. Notably, EGPA patients with VTE often present with thrombocytopenia due to consumption, a finding not typically expected during disease exacerbation. Venous thrombosis generally requires both anticoagulation and immunosuppressive treatment. Although our review indicates a favorable prognosis for AVTE, the small number of reported cases prevents us from drawing definitive conclusions. Future studies should explore the efficacy of mepolizumab and other eosinophil-targeted therapies for AVTE, in addition to investigating the roles of anticoagulation and antiplatelet treatments.